2012
DOI: 10.1159/000339883
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Epoxide Hydrolase Inhibition Exhibits Antihypertensive Actions Independently of Nitric Oxide in Mice with Renovascular Hypertension

Abstract: Objective: The present study was performed to examine whether the blood pressure (BP)-lowering effects of soluble epoxide hydrolase (sEH) inhibition in two-kidney, one-clip (2K1C) Goldblatt hypertension are nitric oxide (NO) dependent. Methods: Mice lacking the endothelial NO synthase (eNOS) gene (eNOS–/–) and their wild-type controls (eNOS+/+) underwent clipping of one renal artery. BP was monitored by radiotelemetry and the treatment with the sEH inhibitor cis-4-[4-(3-adamantan-1-yl-ureido)cyclohex-yloxy]-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 66 publications
4
40
0
Order By: Relevance
“…On the subsequent measurement of the activity of sEH, the present study demonstrated for the first time, to the best of our knowledge, that the 20-HETE increased the protein activity of sEH in the liver and kidney of the hypertensive CYP4F2 transgenic mice. Consistently, previous studies have shown that the protein expression of sEH is upregulated in certain hypertensive models, including two-kidney-one-clip and angiotensin-II infusion hypertension (18)(19)(20), however, the mechanism remains to be elucidated. It has been reported that proinflammatory cytokines elevate the protein level of sEH (13).…”
Section: Discussionsupporting
confidence: 56%
“…On the subsequent measurement of the activity of sEH, the present study demonstrated for the first time, to the best of our knowledge, that the 20-HETE increased the protein activity of sEH in the liver and kidney of the hypertensive CYP4F2 transgenic mice. Consistently, previous studies have shown that the protein expression of sEH is upregulated in certain hypertensive models, including two-kidney-one-clip and angiotensin-II infusion hypertension (18)(19)(20), however, the mechanism remains to be elucidated. It has been reported that proinflammatory cytokines elevate the protein level of sEH (13).…”
Section: Discussionsupporting
confidence: 56%
“…One group received TPPU alone (Ang II + TPPU animals) to control for the previously reported anti-hypertensive effects associated with sEHIs. 37, 38, 44 In order to provide evidence for sEH inhibition, we determined the TPPU concentration in blood samples that were collected at the end of each week after Ang II infusion. Even though we observed a mild accumulation of TPPU, the difference in TPPU levels on day 7 vs .…”
Section: Resultsmentioning
confidence: 99%
“…For example, some oxylipins produced from arachidonic acid or linoleic acid have been associated with inflammation, [3][4][5] tissue damage, 6,7 vasoconstriction, 8,9 and oxidative stress. 10 In contrast, the epoxyeicosatrienoic acids (EETs) produced from arachidonic acid are endothelial-derived hyperpolarizing factors that are associated with vasodilation and natriuresis 11,12 and may indirectly propagate vasodilation [13][14][15] by activating endothelial nitric oxide synthase. 16,17 EETs can be rapidly metabolized to dihydroxyeicosatrienoic acids (DHETs) by the enzyme soluble epoxide hydrolase (sEH), resulting in a concomitant loss of vasodilation.…”
Section: July 2014mentioning
confidence: 99%
“…18,19 sEH also converts the protoxins, epoxyoctadecenoic acids, to the dihydroxyoctadecenoic acids, which are potent cytotoxic and proinflammatory metabolites. [20][21][22] Because products of sEH propagate loss of vascular relaxation and promote inflammation, targeting sEH inhibition pharmacologically has been used successfully to reduce blood pressure, 12,17,23 hypertension-associated renal damage, 17 and infarction size 23 in animal models. The proposed relationship between epoxygenase-derived oxylipins and hypertension is depicted in Figure 1.…”
Section: July 2014mentioning
confidence: 99%
See 1 more Smart Citation